Coral Recruitment, Survival and Growth of Coral Species at Pari Island, Thousand Islands, Jakarta : A Case Study of Coral Resilience - Abrar, Muhammad; Zamani, Neviaty P (Journal of Indonesian Coral Reefs, 2011)
Research concerning survival and growth of coral recruits has been conducted in Pari Islands, Kepulauan Seribu, Jakarta , from March to November 2010, which purpose to determined the effect of biotic and abiotic factors on coral recruitment survival and growth. We observed two life form of coral recruit, Massive and Branching within a transcect area of 2 meter x 70 meter at 5-7 meter depth. Furthermore, for each life form, the coral recruit was grouped in 3 classes, Small(<3cm), Medium (3-6 cm), and large (> 6 cm and 10cm) and all colonies were marked by plastic tag. Coral recruits in this study site were diverse with species diversity reaching 14 genera from 9 families, consisting of 9 genera at ST1-Pari site and 8 genera at ST2-Tikus Site which there were 2 genera founded at each site, Porites and Fungia, and genera of Faviidae were the most dominate, Diversity of coral recruits was moderate level with 1,85 diversity index at ST1-Pari Site and 1,59 at ST2-Tikus Site. The growth of coral recruitment was variated, according to the colony form and size class, which the highest growth of massive colonies to 4.4 mm/month in the small size and branching corals. Survival fo medium size colonies was lower compared to the other categories.